Machine Learning Modeling for Spatial-Temporal Prediction of Geohazard - Ma, Junwei; Dou, Jie (Sensors (Basel, Switzerland), 2023)
Geohazards, such as landslides, rock avalanches, debris flow, ground fissures, and ground subsidence, pose significant threats to people's lives and property [...].Geohazards, such as landslides, rock avalanches, debris flow, ground fissures, and ground subsidence, pose significant threats to people's lives and property [...].